QEEG Theta Cordance in the Prediction of Treatment Outcome to Prefrontal Repetitive Transcranial Magnetic Stimulation or Venlafaxine ER in Patients With Major Depressive Disorder. (April 2015) - Bares, Martin; Brunovsky, Martin; Novak, Tomas; Kopecek, Miloslav; Stopkova, Pavla; Sos, Peter; Höschl, Cyril
The aims of this double-blind study were to assess and compare the efficacy of quantitative electroencephalographic (QEEG) prefrontal theta band cordance in the prediction of response to 4-week, right, prefrontal, 1-Hz repetitive transcranial magnetic stimulation (rTMS) or venlafaxine ER in patients with major depressive disorder (MDD). Prefrontal QEEG cordance values of 50 inpatients (25 subjects in each group) completing 4 weeks of the study were obtained at baseline and after 1 week of treatment. Depressive symptoms were assessed using Montgomery-Åsberg Depression Rating Scale (MADRS) at baseline and at week 1 and 4. Treatment response was defined as a ≥50% reduction in baseline MADRS total score. All responders (n = 9) and 6 of 16 nonresponders in the rTMS group had reduced cordance at week 1 ( P < .01). Reduction of theta cordance value at week 1 was detected in all responders (n = 10) to venlafaxine ER, but only in 4 of 15 nonresponders ( P = .005). The comparison of the areas under the curve of cordance change for prediction of response between rTMS (0.75) and venlafaxine ER (0.89) treated groups yielded no significant difference ( P = .27). Our study indicates that prefrontal QEEG cordance is a promising tool not only for predicting the response to certain antidepressants but also to rTMS treatment, with comparable predictive efficacy for both therapeutic interventions.